The range of stylistic strategies employed by L. Gutauskas in his novel "Wolf Teeth Beads" (Book Three) - Anilionytė, Jūratė (Respectus Philologicus, 1999)
This work discusses stylistic devices in L. Gutauskas’s "Wolf Teeth Beads" (Book Three). The author uses striking ways to develop characters and present their ideas. His stylistic means, rare among Lithuanian writers, can be distributed into two groups: 1) idiosyncratic punctuation, such as an exceptionally large number of exclamation marks, question marks, commas, ellipses marks, and so forth; 2) unusual graphics, such as varying font size and non-traditional paragraphing. Since such devices are more and more widely employed by contemporary writers, they deserve further attention from linguists, writers, and literary researchers.